Implementasi Peraturan Bupati Lombok Timur Nomor 41 Tahun 2020 Tentang Pencegahan Perkawinan Usia Anak Di Desa Sakra Selatan Kecamatan Sakra Kabupaten Lombok Timur - Saepul Rahman; Sri Karyati; Dhina Megayati (Unizar Recht Journal (URJ), 2024)
Penelitian ini bertujuan untuk mengkaji Implementasi  Peraturan Bupati Lombok Timur Nomor 41 Tahun 2020 Tentang Pencegahan Perkawinan Usia Anak Di Desa Sakra Selatan Kecamatan Sakra Kabupaten Lombok Timur serta hambatan dalam implementasinya di Masyarakat. Peneliti ini merupakan penelitian hukum empiris yang menggunakan metode kualitatif. Berdasarkan hasil kajian menunjukkan bahwa implementasi Peraturan Bupati Lombok Timur Nomor 41 Tahun 2020 Tentang Pencegahan Perkawinan Usia Anak Di Desa Sakra Selatan Kecamatan Sakra Kabupaten Lombok Timur belum diterapkan secara maksimal meskipun telah disahkannya peraturan pelaksana di Tingkat desa yakni peraturan desa Sakra Selatan tentang Pencegahan Perkawinan Pada Usia Anak. Penelitian menunjukkan bahwa Pemerintah desa sakra selatan berupaya untuk meminimalir pernikahan usia anak dengan bekerjasama dan bersinergi dengan pihak terkait yaitu bekerjasama dengan Kantor Urusan Agama, Badan Kependudukan Keluarga Berencana Nasional (BKKBN), Pihak sekolah, Tim Penggerak PKK untuk meningkatkan pemahaman kepada masyarakat tentang dampak negative dari perkawinan usia anak. Kata Kunci : Pencegahan Perkawinan Usia Anak, Peraturan Bupati ABSTRACTThis study aims to find out the implementation of East Lombok Regent Regulation Number 41 of 2020 concerning the Prevention of Child Marriage in South Sakra Village, Sakra District, East Lombok Regency? And what are the obstacles in the implementation of East Lombok Regent Regulation Number 41 of 2020 concerning the Prevention of Child Marriage and How to Overcome These Obstacles? This type of research is empirical legal research that uses qualitative methods. The data sources used are primary and secondary data, as well as data, and the internet related to research in South Sakra Village, Sakra District, East Lombok Regency. Based on the analysis of the data conducted, it was concluded that the results of the research on the Implementation of East Lombok Regent Regulation Number 41 of 2020 concerning the Prevention of Child Marriage in South Sakra Village, Sakra District, East Lombok Regency have accommodated in the form of a Perdes concerning the Prevention of Child Marriage. However, in terms of the implementation of Perdes, it is still in the socialization stage, and until now the government of South Sakra Village, Sakra District, East Lombok Regency based on the results of research shows that Perdes has not been maximally socialized in the community. Obstacles in the Implementation of East Lombok Regent Regulation Number 41 of 2020 concerning the Prevention of Child Marriage and Solutions to overcome these obstacles. The main cause is because of the lack of understanding of the community about the regulation itself and because in South Sakra village which is mostly ordinary people so that the community only adheres to customary law and religious law that regulates it. and lack of socialization from government agencies related to the impact caused. Then efforts were made by the South Sakra Village Government, Sakra District, East Lombok Regency to minimize child marriage, by collaborating and synergizing with related parties, namely in collaboration with the Office of Religious Affairs, the National Family Planning Population Board (BKKBN), schools, the PKK Mobilization Team to conduct counseling and socialization to the community by involving parents and adolescents with the aim of providing understanding to the Participants in reducing the divorce rate due to early marriage, while emphasizing to participants to prioritize education for children.